PENGARUH GOOD CORPORATE GOVERNANCE DAN SUSTAINABILITY REPORT TERHADAP FIRM VALUE - Raihan Aryana Putra; Dila Angraini (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This research aims to examine the influence of Good Corporate Governance and Sustainability Report on Firm Value (Price Book Value). This research uses secondary data with a sample of Sri-Kehati Index companies during the 2018-2022 period. The index used in collecting Good Corporate Governance data uses the percentage of independent commissioners and the number of audit committees. The Sustainability Report uses the 2018 Global Reporting Initiative (GRI) Standards. Sampling was carried out using the purposive sampling method. This research uses a sample of 51 company financial reports and Sustainability Reports. The data analysis method used in this research is the panel data regression method using Eviews version 12 software to process the data. Simultaneous test results prove that Good Corporate Governance proxies for the Independent Commissioner and Audit Committee and the Sustainability Report have a significant effect simultaneously. The partial test results prove that Good Corporate Governance as a proxy for Independent Commissioners has no effect on Firm Value. Meanwhile, the Good Corporate Governance proxy of the Audit Committee has a positive effect on Firm Value and the Sustainability Report has a negative effect on Firm Value.